Portrayals of economic exchange in the book of Kings - Nam, Roger S. (Biblical Interpretation Series, 2012)
With the growing proliferation of literature concerning the social world of the Hebrew Bible, scholars continue to face the challenge of a proper understanding of ancient Israel's economies. Portrayals of Economic Exchange in the Book of Kings is the first monographic study to use an anthropological approach to examine the nature of the economic life behind the biblical text. Through Karl Polanyi's paradigm of exchange as a methodological control, this book synthesizes Semitic philology with related fields of Levantine archaeology and modern ethnography. With this interdisciplinary frame, Nam articulates a social analysis of economic exchange, and stimulates new understandings of the biblical world.